Effects of human activities on annual change of water quality by depth profile of Pasak Jolasid Reservoir, Thailand - Yupin Phoondee (2018)
Copyright © EM International. Pasak Jolasid Reservoir is the main water supply resource in Lopburi Province Thailand. The water quality in this reservoir was monitored through the use of a depth profile from November 2009 to October 2010. Results of the study were achieved by assessing certain specific physico-chemical properties. Water samples were collected from the surface down to the bottom (2 m interval) of the reservoir every 2 weeks. As a result, it was found that the average amount of dissolved oxygen increased according to the depth of the reservoir. However, the amount at the surface level was found to be higher than that at the lower depths due to the occurrence of the process of photo synthesis by phytoplankton, which was in high abundance on the surface of the water. Moreover, we also found that aquaculture and agriculture activities were taking place around this reservoir, which we determined were the main reasons for the contamination of organic matter at the surface level and which also supported the growth of phytoplankton and induced high DO values at the surface level. The contamination of organic matter was also an important determination for high conductivity, BOD5, nitrate-nitrogen, ammonium-nitrogen and SRP values that were recorded at the surface; however, the average values were found to have increased according to the depth of the reservoir. Therefore, the overall water quality could be classified as mesotrophic status or of moderate water quality according to the Applied Algal Research Laboratory physico-chemical score. According to the standard water quality of Thailand, it is considered to be in the second and third categories. Therefore, the water in the reservoir could be used for household consumption after proper treatment.